La Fundación Rockefeller y la Institución Cultural Española de Buenos Aires frente el exilio republicano español en la Argentina: El caso de Claudio Sánchez Albornoz - Lida, Miranda (2020)
The Republican Scientific Exile to the Americas has been widely studied. In this context, the case of historian Claudio Sánchez Albornoz was quite exceptional because of the complex strategy that led to his arrival in Argentina. He was supported by the Rockefeller Foundation (RF), whose role has barely been studied. Another key player was the Institución Cultural Española de Buenos Aires (ICEBA). Thanks to the archives at Buenos Aires University and ICEBA (and correspondence with the RF), we can trace the network that made his arrival in Argentina possible, with the support of both institutions.